2019
DOI: 10.1097/coc.0000000000000635
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiotherapy for Oligometastatic Prostate Cancer Recurrence

Abstract: Purpose: The purpose of this study was to evaluate the treatment efficacy of stereotactic body radiotherapy (SBRT) in oligometastatic prostate cancer recurrence and to assess whether there is any relationship between biologically effective dose (BED) and local control (LC). Materials and Methods: Eligible studies were identified on Medline, Embase, and the Cochrane Library, and the proceedings of annual meetings through May 2019 were also identified. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Certainly, data supporting MDT, in particular SBRT, could not be ignored even if provided mostly by retrospective studies. A recent systematic review by Viani et al [25] , including 23 observational studies with a total of 1441 lesions treated with SBRT, showed excellent rates of local control (0.976; 95% CI, 0.96–0.98) and ADT-free survival of 20.1 mo, with low rates of acute and late moderate-to-severe toxicity events (1.3% and 1.2%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, data supporting MDT, in particular SBRT, could not be ignored even if provided mostly by retrospective studies. A recent systematic review by Viani et al [25] , including 23 observational studies with a total of 1441 lesions treated with SBRT, showed excellent rates of local control (0.976; 95% CI, 0.96–0.98) and ADT-free survival of 20.1 mo, with low rates of acute and late moderate-to-severe toxicity events (1.3% and 1.2%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…SBRT is widely accepted as an effective treatment for oligometastases and PC patients may benefit from MDT in both hormone-sensitive and castration-resistant settings. Patients affected by nodal-exclusive OMD are typically characterized by a more indolent disease than those affected by polymetastatic or visceral metastases: in this setting, local treatments, such as SBRT, are able to delay the start of systemic therapy, prolong its duration, or postpone the switch to a subsequent treatment line [19,[22][23][24]. No statistical differences were recorded between the two groups in CRFS, PMFS, and LPFS.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PC nodal metastases generally have a better prognosis than those with bone or visceral metastases [ 18 ]. The use of SBRT is well-established in clinical practice for oligometastatic pelvic lymph nodes due to its excellent local control [ 19 ]. However, only a few studies have evaluated the use of MDT on para-aortic lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…This important observation was further substantiated by a comprehensive metaanalysis spanning both trials. Consequently, this collective body of evidence has firmly established a gold standard of care in the local control of the primary tumour with radiotherapy for patients characterized by synchronous low-volume metastases [34].…”
Section: Radiotherapy To Primary Tumour In Low Volume Metastasismentioning
confidence: 99%